UJI EFEK JUS TAOGE TERHADAP KADAR KOLESTEROL TIKUS (Rattus norvegicus) JANTAN HIPERLIPIDEMIA - Sukmawati Sukmawati; A. Ririn Perawanti Asgap (Fakultas Farmasi UMI, 2017)
The test effect of Taoge Juice on Cholesterol Level of Rat (Rattus norvegicus) Male Hyperlipidemia.This research purpose to know and to fix the concentration of Taoge Juice which have hypolipidemia effect at rat (Rattus norvegicus) male, that administered orally has been conducted. This research used 15 rat male and divided to 5 groups, and each group consist 3 rat male. First group given Na.CMC as control, second group given simvastatin as standard of comparison.The third, fourth and fifth groups given Taoge Juice with 30 %, 60%, and 90 % respectively. This research done by measuring the normal cholesterol level, induced by propiltiurazil and goat lipid and given by NaCMC, Taoge Juice with 30%, 60%, and 90% concentration and standard of comparison (Simvastatin). This cholesterol level determing by using Human Analyzer. Then do the analyzing data. Besed on analyzed data obtain that control group is significantly (p<0,05) with 30%, 60%, dan 90% group and standard of comparison group. While the group of Taoge Juiceand standard of comparison group not significantly (p>0,05). By analysis of the research result that Taoge Juice have hypolopidemia effect on 30%, 60%, dan 90% concentration.